EMG variance during polysomnography as an assessment for REM sleep behavior disorder. - Burns JW; Consens FB; Little RJ; Angell KJ; Gilman S; Chervin RD (Sleep)
STUDY OBJECTIVES: In a previous study, we validated a polysomnographic assessment for REM sleep behavior disorder (RBD). The method proved to be reliable but required slow, labor-intensive visual scoring of surface electromyogram (EMG) activity. We therefore developed a computerized metric to assess EMG variance and compared the results to those previously published for visual scoring, bed partner-rated RBD symptom scores, and clinical assessments by sleep medicine specialists. DESIGN: Retrospective validation of new computer algorithm. SETTING: Sleep research laboratory PARTICIPANTS: Twenty-three subjects: 17 with neurodegenerative disorders (9 with probable or possible RBD), and 6 controls. INTERVENTIONS: N/A METHODS: We visually scored 2 consecutive nocturnal polysomnograms for each subject. A computer algorithm calculated the variance of the chin EMG during all 3-second mini-epochs, and compared variances during REM sleep to a threshold defined by variances during quiet NREM sleep. The percentage of all REM mini-epochs with variance above this threshold created a metric, which we refer to as the supra-threshold REM EMG activity metric (STREAM) for each subject. RESULTS: The STREAM correlated highly with the visually-derived score for RBD severity (Spearman rho = 0.87, P < 0.0001). A clinical impression of probable or possible RBD was associated to a similar extent with both STREAM (Wilcoxon rank sum test, P = 0.009) and the visually-derived score (P = 0.018). An optimal STREAM cutoff identified probable or possible RBD with 100% sensitivity and 71% specificity. The RBD symptom score correlated with both STREAM (rho = 0.42, P = 0.046) and the visual score (rho = 0.42, P = 0.048). CONCLUSIONS: These results suggest that a new, automated assessment for RBD may provide as much utility as a more time-consuming manual approach.